PREVALENCE OF MALASSEZIA SP. IN THE EARS OF ASYMPTOMATIC DOGS AND DOGS WITH OTITIS ATTENDED IN THE VETERINARY HOSPITAL CLINIC IN LAGES/SC IN THE PERIOD OCTOBER TO DECEMBER 2000. - Vaz, Adil Knackfuss; Zamban, Adriana L. M. (Revista de Ciências Agroveterinárias, 2002)
The yeast Malassezia pachydermatis is very important in Veterinary Medicine, due to its presence in the ears and skin of dogs. The objective of this study was to determine the prevalence of Malassezia sp. in the external ear of dogs with otitis and asymptomatic dogs, and to establish a correlation among clinical otitis, direct microscopic examination and culture. It was collected the cerumen of the ears with swabs for direct microscopic examination and with the ginecological brush for culture in Sabouraud medium with olive oil at 25°C. It was observed a larger ocurrence of Malassezia sp. in ears with symptons of otitis and positive cultures which showed 26 from to 50 yeast cells in 5 microscopic fields in the direct examination.